2013
DOI: 10.1007/s00106-013-2752-x
|View full text |Cite
|
Sign up to set email alerts
|

Video-Kopfimpulstest oder thermische Prüfung?

Abstract: The video head impulse test (vHIT) is a new method for investigating vestibular function that is currently poorly studied in terms of its value for clinical diagnosis in otolaryngology. Both the caloric irrigation and vHIT serve to evaluate the horizontal vestibulo-ocular reflex. In the present study, caloric irrigation and vHIT were compared in 46 patients with vestibular schwannoma. Caloric irrigation exhibits a higher sensitivity than vHIT (72% versus 41%) and both tests show only a moderate correlation. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…The same group recently examined 46 patients with VS and showed that caloric irrigation exhibits a higher sensitivity than HIT (72% versus 41%) and both tests show only a moderate correlation. Tumour size and hearing level were significantly correlated with caloric abnormalities but not with HIT findings [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same group recently examined 46 patients with VS and showed that caloric irrigation exhibits a higher sensitivity than HIT (72% versus 41%) and both tests show only a moderate correlation. Tumour size and hearing level were significantly correlated with caloric abnormalities but not with HIT findings [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is now clear that many patients (especially those with Menière’s disease) do have normal horizontal canal function—as shown by vHIT, responses to high-acceleration horizontal head rotation, but have reduced or absent caloric responses (7276). It has been suggested that this dissociation between vHIT and caloric results may be an indicator of Menière’s disease (77, 78).…”
Section: Practical Aspects and Potential Pitfalls Of Video Head Impulmentioning
confidence: 99%
“…VS initially show a pathological UW and a normal vHIT. However, with increasing size the vHIT might become pathological [69][70][71]. It is controversially discussed if UW is a predictor for tumour size [70,72] or not [73].…”
Section: Vestibular Schwannoma (Vs)mentioning
confidence: 99%
“…However, with increasing size the vHIT might become pathological [69][70][71]. It is controversially discussed if UW is a predictor for tumour size [70,72] or not [73]. It was shown that the VOR gain of vHIT is not correlated with the tumour size [70] but rated together with the CI there was a correlation.…”
Section: Vestibular Schwannoma (Vs)mentioning
confidence: 99%